TINDAK TUTUR DIREKTIF DALAM SENI PERTUNJUKAN JAWA - Sutarno Haryono (Institut Seni Indonesia Surakarta, 2019)
The follow-up directive is a speech speaker with the intention that the partner speak or not perform the action in accordance with the intent of the speakers. The follow-up directive uses your substitute word as the perpetrator, although the word is not always present in every utterance. The follow-up directive is prospective, we are unlikely to have someone else do something in the past. As with some other types of greeting, the follow-up directive suspects a number of circumstances related to the person being called and the context of the situation (background). The backdrop depicts the place where events occur, the current atmosphere of the event, and the timing of events that include morning, noon, night or all time (time of day) and period of time, which will come, or that have been Then (time of period).Keywords: Speakers, speaking partners, speech, follow-up directive,